Textile designers : at the cutting edge. - Quinn, Bradley, ....- (London : Laurence King, 2009)
Featuring designers chosen for their contributions to fashion textiles and interior fabrics, the book showcases today's most forward-thinking and exciting work that signals new directions in textile practice and the emergence of new textile forms and fibre technologies. Whether speaking from style capitals, such as London, Paris, Milan, Madrid, Berlin, Tokyo, and New York, or in less-trafficked cities, the designers describe their output and inspirations in their own words. The book not only features images of completed designs, but also previously unseen archive material, such as work-in-progress photographs and digital drawings. These unique visuals create a stylish picture of today's textiles, as well as an essential reference guide for those interested in contemporary textile design.
Keywords: Ontwerpers; Textiel